Implications of queuing time on the carrying capacity and satisfaction of theme park visitors - Machado, Ana Carolina Padua; Lobo, Heros Augusto Santos (Revista Turismo em Análise, 2019)
The theme parks are leisure structures created from the use of technology and based on specific themes, - designed to attract large contingents of people in a relatively restricted space. They consist of services to visitors such as parking and ticket office, including their biggest finality, which are the attractions. The logic of these parks’ functioning leads to the formation of queuing at various moments of the visitation. In this context, this research aimed to develop a panorama about the perception of the theme parks’ visitors about the waiting time in the queuing of the main services offered in these establishments. To do that, prestructured questionnaires were applied to be completed online, with people who already attended theme parks. The collected data were described with statistical support – linear regression and correlation matrix of similarity – as well as analyzed and related to concepts of satisfaction on visitation, social carrying capacity and experience quality. The results showed that the waiting times in the queues did not affect significantly the respondents’ perception, since the evaluations in the questionnaire were mostly positive. It can be concluded that the waiting time in queues does not affect negatively the perception of crowd and the social carrying capacity of the theme parks in the perception of Brazilian visitors. Keywords: Social carrying capacity; Crowded perception; Tourism of Experience.